2003
DOI: 10.1161/01.cir.0000103123.66264.fe
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Type 2 Diabetes Mellitus on Sympathetic Neural Mechanisms in Hypertension

Abstract: Patients with EHT+DM2, EHT, or DM2 had central sympathetic hyperactivity, although plasma insulin levels were raised only in EHT+DM2 and DM2. The combination of EHT and DM2 resulted in the greatest sympathetic hyperactivity and level of plasma insulin, and this hyperactivity could constitute a mechanism for the increased risks of this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
181
3
10

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(218 citation statements)
references
References 39 publications
15
181
3
10
Order By: Relevance
“…For instance, firstly, raised plasma insulin levels and insulin resistance have been related to sympathetic hyperactivity and could be associated with hypertension and obesity. 3,8,42,43 However, the four groups of the present study were not obese and had similar BMI and waist circumference. Furthermore, the groups of women and men with hypertension had similar levels of arterial blood pressure.…”
Section: For Hypertensive Women (F-eht) and Men (M-eht) Normotensivementioning
confidence: 57%
“…For instance, firstly, raised plasma insulin levels and insulin resistance have been related to sympathetic hyperactivity and could be associated with hypertension and obesity. 3,8,42,43 However, the four groups of the present study were not obese and had similar BMI and waist circumference. Furthermore, the groups of women and men with hypertension had similar levels of arterial blood pressure.…”
Section: For Hypertensive Women (F-eht) and Men (M-eht) Normotensivementioning
confidence: 57%
“…The details of such sessions have been published previously [16,24]. Briefly, all investigations were performed under similar conditions between 09.00 and 12.00 hours in order to avoid circadian autonomic variation.…”
Section: Methodsmentioning
confidence: 99%
“…Past studies in patients with type 2 diabetes but no neuropathy have reported an increase or a decrease in plasma noradrenaline levels [13][14][15] and an increase in peripheral muscle sympathetic nerve activity (MSNA) [16]. Also, there are reports that patients with type 2 diabetes have either normal or decreased levels of heart rate variability [14,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that luseogliflozin can effectively decrease the HR in patients with higher baseline HR. Some patients with type 2 diabetes mellitus have elevated central sympathetic activity, which is exacerbated by a malfunction of the negative feedback mechanism as a result of decreased sensitivity of baroreceptor reflexes5, 6. This results in elevation of peripheral sympathetic activity in the heart, leading to an increase in resting HR.…”
mentioning
confidence: 99%